Characterisation of aspergillus section flavi and development of aflatoxins level detection methods in food grains and poultry feeds from Malaysia and Nigeria - Salisu, Baha’uddeen (2022)
Aspergillus section Flavi (ASF) and their aflatoxins are among the most critical food and feed contaminants with deleterious economic and public health impacts. It contributes to about 20% of global cancer-related deaths annually. However, research data is lacking from most states in Malaysia and Nigeria, where ASF contamination is usually high. This study determines the bioburden and distribution of mycoflora in 660 Malaysian and Nigerian food grains and poultry feeds by utilising microbiological dilution plating techniques; in identifying, classifying, and screening the isolated ASF for aflatoxigenicity by phenotypic, biochemical, molecular, and phylogenetics methods. In addition, simplified chromatographic (Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC)) and spectroscopic (Attenuated Total Reflectance – Fourier Transformed Infrared Spectroscopy (ATRFTIR)) aflatoxin quantification methods were developed and validated; hence applied to determine the aflatoxins level in the samples. The average dietary exposure risks to aflatoxins (DERA) and attributable liver cancer (HCC) risks were also determined. A total of 142 and 185 filamentous fungal isolates with average bioburden of 8.9 x 104 ± 1.6 x 105 to 1.0 x 106 ± 2.5 × 105 CFU/g and 1.2 x 105 ± 1.7 x 105 to 4.0 x 105 ± 5.8 x 104 CFU/g were obtained from the food grains and poultry feeds from Malaysia and Nigeria, respectively. Based on the phenotype, extrolites and gene sequence data (β – tubulin gene and nuclear ribosomal internal transcribed spacer (ITS) gene), 74 isolates (Malaysia = 27, Nigeria = 47) were identified as ASF (60 A. flavus and 14 A. oryzae), of which 47 (Malaysia = 13, Nigeria=34) produced aflatoxins on solid media and possessed the aflatoxin biosynthesis genes (aflR, aflP, aflD and aflM). On the other hand, the developed chromatographic and spectroscopic methods showed high accuracy and sensitivity in quantifying aflatoxins in the order HPLC (R2 > 99.9%) > FTIR (R2 = 99.59%) > TLC (R2 > 99%). The HPLC showed that the levels of aflatoxins (8.68 to 77.40 ng/g) in samples from Malaysia signified low DERA (3.27 to 35.88 ng of aflatoxins/KgBw/day) and HCC risks (1.67 to 18.31% incidence of HCC/100,000 peoples/year) compared the levels of aflatoxins (0.21 to 114.41 ng/g) in samples from Nigeria (mean DERA = 23.04 to 50.08 ng/KgBw/day, HCC risk = 26.61 to 57.94% incidence of HCC/100,000 peoples/year). Results showed that (i) improved aflatoxin extraction and quantification methods (FTIR, TLC and HPLC) in food grains and poultry feeds were developed and validated in this study with accuracy values of 90% to 103%; (ii) A. flavus and A. oryzae are the main ASF species identified in the samples, with aflatoxigenic chemotypes being significantly higher than the nonaflatoxigenic groups and (iii) significant number of the samples analysed have fungal bioburden and aflatoxins above the international regulatory limit which could lead to above than 10% HCC cases in the study regions. Hence, fungal/aflatoxin control and prevention strategies should be strengthened in the study regions.